TESTING OF FINANCIAL PERFORMANCE CHANGES IN NATIONAL FINANCING COMPANIES IN THE PRE AND PAST COVID-19 TIMES (Study on Companies in the Sub-Sector of Financing Institutions Listed on the Indonesia Stock Exchange 2018-2022) - Iklil; Rico Nur Ilham; Chairil Akhyar; Zulfan (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
This research examines the differences in financial performance before and after the COVID-19 pandemic among financial sector enterprises listed on the Indonesia Stock Exchange from 2018 to 2022. The socio-economic impact of COVID-19 has affected various sectors of the economy, including both industrial and service sectors, thereby influencing productivity and subsequent company performance. It is noteworthy that the highest growth in financial performance for financing enterprises occurred in 2022, following declines in 2019 and 2020, with a particularly drastic decrease in 2020. The independent variables in this study include financial performance, financing enterprises, liquidity ratio, solvency, profitability, and dividend payout, with COVID-19 as the dependent variable. Data collection utilized secondary data obtained from the official website of the Indonesia Stock Exchange (IDX) and the Annual Reports of each company. The study encompassed 18 sample enterprises listed on the IDX. This research employed a quantitative method, utilizing descriptive statistics and paired sample t-tests to analyze liquidity, solvency, profitability, and dividend payout using the Eviews 13. Findings indicate no significant differences in liquidity, solvency, profitability, and dividend payout ratios before and after the pandemic. These results contradict previous research findings showing varied impacts of COVID-19 on financial performance. The study concludes that financial enterprises effectively managed their assets during the pandemic. Recommendations for future research include expanding the sample size and considering additional financial performance indicators to further explore the impact of COVID-19 on financial performance.